The reference genome and organelle genomes of wasabi (Eutrema japoniacum) - Liu, Hexia; Qiao, Qinghua; Ye, Xiaoxia; Guo, Yipeng; Ye, Baojian; Xu, Qiuyuan; Zhou, Xingwen; Li, Bo (Frontiers in Genetics, 2022)
Wasabi (Eutrema japonicum) is one of the most famous vegetable crops in the family Brassicaceae. However, a limited genomic resource is available, which hinders genomic breeding and understanding of the genetic basis of vital traits. Here, we generated the genome assembly of wasabi using the hybrid genome assembly strategy, which combined the Nanopore long reads and Illumina reads. The genome assembly contains 687M bp and 39,534 high-quality annotated gene models. Besides, we annotated 68.85% of the genomic sequences as repetitive elements, including 43.72% of retrotransposons and 18.99% of DNA transposons. Using the customized pipeline, we also generated the complete organelle genomes of wasabi. This reference genome could provide essential genomic resources for evolution, breeding, and exploring the unique biological traits of wasabi.